A beautiful mess : weekday weekend : how to live a healthy veggie life ... and still eat treats - Chapman, Emma; Larson, Elsie (Chronicle Books, 2017)
"If you are looking for a great first step toward eating better, or you're in need of a healthy reset button, please join us in Weekday Weekend eating! We're making delicious plant-based food all week and then spending our weekend enjoying a few treats. You're gonna love it -- and you can do this. Come eat with us." -- Back cover.